Physiological traits and population dynamics of Schizothorax niger (Heckel, 1838): Insights from Dal Lake and the Jhelum River, Kashmir, Himalayan region - Narayanan Karthik; Farooz Ahmad Bhat; Imtiyaz Qayoom; N. Jayakumar; C. Sudhan; P. Seenivasan; Divya Meril; Ishrat Mohd; Asra Mattoo (Journal of Fish Biology, 2025)
This study examines the physicochemical characteristics, morphometric features, biometric growth parameters, biological indices, physiological parameters, and biochemical profiles of Schizothorax niger population. The physicochemical analysis revealed a maximum temperature of 12.93 ± 1.33°C and hardness of 156.53 ± 12.82 mg/L in Dal Lake, whereas the Jhelum River had a minimum level of 10.94 ± 1.12°C temperature and 128.31 ± 11.62 mg/L of hardness. Dal Lake had a neutral pH (7.5 ± 0.2) and lower dissolved oxygen (6.8 ± 0.4 mg/L) compared to the Jhelum River (pH 7.2 ± 0.3; dissolved oxygen 7.5 ± 0.5 mg/L). Morphometric analysis showed significant differences ( p b = 3.15) than the Jhelum River ( b = 2.98). Biological indices revealed gender‐based variations in the gonado‐somatic index (GSI) and hepato‐somatic index (HSI), with GSI being higher in Dal Lake (0.21 ± 0.02) and HSI in the Jhelum River (1.04 ± 0.09). Haematological and biochemical analyses showed significant differences in parameters such as haematocrit (Dal Lake: 29.2 ± 2.1%; the Jhelum River: 32.4 ± 1.8%), glucose (Dal Lake: 85.3 ± 5.4 mg/dL; the Jhelum River: 68.1 ± 4.2 mg/dL), and total protein (Dal Lake: 6.2 ± 0.4 g/dL; the Jhelum River: 5.8 ± 0.3 g/dL) between sites. These findings provide valuable insights into the physiological traits and population dynamics of S. niger , informing species‐specific conservation strategies and ecosystem management practices.